The PBAP remodeling complex is required for histone H3.3 replacement at chromatin boundaries and for boundary functions. - Nakayama, T.; Shimojima, T.; Hirose, S. (Development, 2012)
Establishment and maintenance of epigenetic memories are essential for development. Replacement of canonical histone H3 by its variant H3.3 has been implicated in cellular memory. Drosophila sequence-specific DNA-binding protein GAGA factor and a chromatin factor FACT direct H3.3 replacement in conjunction with H3.3-specific chaperone HIRA at chromatin boundaries to counteract the spreading of silent chromatin. However, little is known about which ATP-driven chromatin remodeling factor is responsible for the H3.3 replacement at chromatin boundaries. Here, we report that GAGA factor associates with the Polybromo-associated Brm (PBAP) remodeling complex, which consists of many Trithorax group proteins, and recruits this complex to chromatin boundaries d1 (which is downstream of w), the Fab-7 DNase-hypersensitive site (HS) 1 of Abd-B and the bxd region of Ubx. Trl-encoding GAGA factor, brm and polybromo/bap180 mutations compromise the H3.3 replacement and boundary functions in a synergistic manner. Furthermore, Polybromo is necessary for generation of the DNase HS at d1, and HIRA functions to restore the alteration. Taken together, we propose that FACT and PBAP complexes are recruited to chromatin boundaries in a GAGA factor-dependent manner, and are needed for H3.3 replacement to execute boundary functions. Our results provide new insight into the function of the trithorax group during development.